2019
DOI: 10.1158/1055-9965.epi-19-0105
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Cigarette Use among Survivors of Smoking-Related Cancers in the United States

Abstract: Background: The prevalence of electronic cigarette (e-cigarette) use and its impact on smoking cessation among cancer survivors in the United States is largely unknown. We sought to estimate the prevalence of e-cigarette use and examine its associations with cigarette smoking and smoking quit attempts among smoking-related cancer survivors in the United States.Methods: We obtained data from the 2014-2017 annual cycles of the National Health Interview Survey for participants with self-reported history of smokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
(33 reference statements)
1
12
1
Order By: Relevance
“… 32 - 36 In addition to reinforcing concerns about cigarette smoking of patients with cancer, this study highlights the occurrence of noncigarette tobacco use. Although only 1% of patients with cancer in this study engaged in this behavior, other studies have found that 3%-25% of patients with cancer are current users of electronic cigarettes, 37 , 38 a number that may increase with time, 39 in part because smokers believe that these products aid smoking cessation. 40 Tobacco use is a deeply entrenched behavior that cancer care providers cannot ignore because of fears of upsetting patients or perceptions of inadequate training.…”
Section: Discussioncontrasting
confidence: 55%
“… 32 - 36 In addition to reinforcing concerns about cigarette smoking of patients with cancer, this study highlights the occurrence of noncigarette tobacco use. Although only 1% of patients with cancer in this study engaged in this behavior, other studies have found that 3%-25% of patients with cancer are current users of electronic cigarettes, 37 , 38 a number that may increase with time, 39 in part because smokers believe that these products aid smoking cessation. 40 Tobacco use is a deeply entrenched behavior that cancer care providers cannot ignore because of fears of upsetting patients or perceptions of inadequate training.…”
Section: Discussioncontrasting
confidence: 55%
“…This study did not ascertain the reason for noncigarette tobacco use, but one could surmise that it is due to the belief these products might aid smoking cessation or be a helpful substitute in places or during times when smoking is prohibited (Popova & Ling, 2013; Shi et al, 2017). Reports of electronic cigarette use in cancer survivors have grown in recent years (Akinboro et al, 2019; Kalkhoran et al, 2018), though research on other products remains rare (see Little et al, 2018 for an exception). Importantly, trial and adoption of electronic cigarettes and the like among cancer survivors who smoke may outpace the rate at which we accumulate empirical evidence of their safety profile and effectiveness for smoking cessation (Kalkhoran & Glantz, 2016; McRobbie et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that 40% of the participants had ever used other tobacco products, with 10% having used an electronic cigarette in the past 30 days. Other studies have found that 3–25% of patients with cancer are current users of electronic cigarettes [ 48 , 49 ]. Future research could further explore whether smoking cessation programs should consider counselling to encourage the use and success of alternative tobacco products in patients who are unable to quit smoking cigarettes.…”
Section: Discussionmentioning
confidence: 99%